Problems of Determining Child Support Obligations in Russian and American - ARTEMYEVA, Y. A; SERGEEVA, V. V (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT The article analyzed the laws of the United States and the Russian Federation in order to determine the key points of protecting the interests of minor children in the divorce of their parents. The purpose is a comparative examination of theoretical and practical problems of the implementation of child support obligations of parents in Russia and the United States. The authors used a combination of philosophical, general and private, scientific methods of cognition of theoretical and empirical material, considering historical, political, and national characteristics. The study has allowed identifying some significant problems.RESUMEN El artículo analizó las leyes de los Estados Unidos y la Federación de Rusia con el fin de determinar los puntos clave para proteger los intereses de los menores en el divorcio de sus padres. El propósito es un examen comparativo de los problemas teóricos y prácticos de la implementación de las obligaciones de manutención infantil de los padres en Rusia y los Estados Unidos. Los autores utilizaron una combinación de métodos filosóficos, científicos generales y científicos privados de cognición de material teórico y empírico, considerando características históricas, políticas y nacionales. El estudio ha permitido identificar algunos problemas importantes.